Development of ZHPV16E7- granzyme B immunoaffitoxin: dual mechanisms targeting hpv16-positive cervical cancer through epithelial-mesenchymal transition inhibition and cell death - Tan, Xiaochun; Yang, Jiani; Li, Yanheng; Wan, Kairong; Feng, Sicong; Jing, Xishang; Xie, Zhenyun; Zhang, Lifang; Li, Wenshu (Frontiers in Immunology, 2025)
IntroductionCervical cancer, predominantly caused by high-risk human papillomavirus (HPV), remains a major global health challenge. HPV16 is the most prevalent type, and its oncoprotein E7 promotes epithelial-mesenchymal transition (EMT), a critical step in metastasis. Current therapies for HPV16-related cancers are often insufficient, highlighting the need for targeted treatments. We engineered a novel immunotoxin, ZHPV16E7-GrB, by fusing an HPV16E7-specific affibody (ZHPV16E7) with the cytotoxic immune effector granzyme B (GrB). This construct was designed for precise targeting and therapeutic activity against HPV16-positive cervical cancer cells.MethodsZHPV16E7-GrB was engineered, expressed in E. coli, and purified. Binding specificity was assessed via ELISA and immunofluorescence using HPV16-positive (SiHa, CaSki), HPV18-positive (HeLa), and HPV-negative (C33A) cervical cancer cells. Functional assays evaluated cell viability (LDH release, luminescence), migration (Transwell), EMT markers (Western blot for E-cadherin, N-cadherin, Vimentin, Snail), apoptosis (TUNEL, flow cytometry, caspase activation), and pyroptosis (SYTOX Green uptake, cytokine release ELISA, GSDME cleavage). Caspase-3 knockdown and in vitro cleavage assays determined pyroptosis mechanisms.ResultsZHPV16E7-GrB exhibited strong binding specificity for HPV16E7. It significantly inhibited cell growth and suppressed EMT in HPV16-positive cells, evidenced by reduced migration and invasion, downregulation of Vimentin and Snail, increased E-cadherin, and decreased N-cadherin expression. Furthermore, ZHPV16E7-GrB induced apoptosis via caspase-3/caspase-8 activation and triggered pyroptosis through direct cleavage of gasdermin E (GSDME), independent of caspase-3, accompanied by membrane rupture and proinflammatory cytokine release. Crucially, ZHPV16E7-GrB demonstrated selective toxicity, effectively killing HPV16-positive cells while sparing non-HPV16-positive cells, minimizing off-target effects.DiscussionThis study highlights the dual mechanism of ZHPV16E7-GrB, inhibiting EMT and inducing cell death (apoptosis and pyroptosis). These findings demonstrate its significant promise as a targeted therapeutic agent for HPV16-associated cervical cancer, addressing critical unmet needs in current treatment strategies.